From apocalypticism to eschatology: a comparative analysis of western “Utilitarianism” and Islamic “Maṣlaḥah” - Mufazzal, Mohammad Abul; Chaudhary, Naseem Fatima (Universitas Ahmad Dahlan, 2024)
By employing Utility tools or moral conducts based on “the greatest good for the greatest number”, the Utilitarian mechanism maximizes the Utility for majority. This ethical theory is evidently grounded in human reason free from any transcendent revelation which is all the way expounded as a purely secular product of renaissance. While, in contrast to “Utilitarianism”, the Islamic “Maṣlaḥah” transcends the spatial structure and materiality to connect the life hereafter, hence the immediate good and bad of this world are but the function for the final good or bad pertaining to the Afterlife. Reviewing and analyzing relevant contents, this paper explores the key differences and similarities between Western “Utilitarianism” and Islamic “Maṣlaḥah”. Firstly, the paper identifies that both “Utilitarianism” and “Maṣlaḥah” aim to promote human welfare and happiness, but differ in their approach to defining and measuring the concept. Secondly, the paper examines the role of reason and revelation in shaping ethical decision-making in both traditions. Finally, it discusses the practical implications of “Utilitarianism” and “Maṣlaḥah” in contemporary societies. While “Utilitarianism” is often associated with individualistic and secular societies, Islamic “Maṣlaḥah” is deeply embedded in Islamic culture and tradition, which emphasizes community values and religious obligations.